PENGARUH ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN, PENERIMAAN KAS, DAN PENGELUARAN KAS TERHADAP PENGENDALIAN INTERNAL - Herni Pujiati; Eggie Shelinawati (Institut Teknologi dan Bisnis Swadharma, 2022)
This study aims to analyze existing accounting information systems, namely implementation procedures that can monitor sales accounting information systems, monitor cash receipts accounting information systems properly, and supervise cash disbursements. This research method uses descriptive quantitative methods, with a non-probability sampling technique, with employees of PT Surya David Susanto as respondents. Data distribution of questionnaires with a sample of 31 respondents. The technique used is the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Coefficient of Determination Test (R2), and Hypothesis Testing (T-Test and F Test). The results of this study are sales accounting information system variables do not affect internal control, cash receipts accounting information system variables affect internal control, and cash disbursements accounting information system variables do not affect internal control. Meanwhile, based on the results of the F test showing F count 12.545 > F table 2.95, it is evident that the variables Sales, Cash Receipts, and cash disbursements simultaneously affect internal control.